The role of genomic islands in Escherichia coli K1 interactions with intestinal and kidney epithelial cells - Yousuf, Farzana Abubakar; Rafiq, Sahar; Siddiqui, Ruqaiyyah Bano *; Khan, Naveed Ahmed * (Elsevier, 2016)
The completion of Escherichia coli K1 genome has identified several genomic islands that are present in meningitis-causing E. coli RS218 but absent in the non-pathogenic E. coli MG1655. In this study, the role of various genomic islands in E. coli K1 interactions with intestinal epithelial cells (Caco-2) and kidney epithelial cells (MA104) was determined. Using association assays, invasion assays, and intracellular survival assays, the findings revealed that the genomic island deletion mutants of RS218 related to P fimbriae, S fimbriae, F17-like fimbriae, non-fimbrial adhesins, Hek and hemagglutinin, protein secretion system (T1SS for hemolysin; T2SS; T5SS for antigen 43), Iro system and hmu system), invasins (CNF1, IbeA), toxins (a-hemolysin), K1 capsule biosynthesis, metabolism (D-serine catabolism, dihydroxyacetone, glycerol, and glyoxylate metabolism), prophage genes, showed reduced interactions with both cell types. Next, we determined the role of various genomic islands in E. coli K1 resistance to serum. When exposed to the normal human serum, the viability of the genomic island deletion mutants related to adhesins such as S fimbriae, P fimbriae, F17-like fimbriae, non-fimbrial adhesins, Hek and hemagglutinin, antigen 43 and T5SS for antigen 43, T2SS, and T1SS for hemolysin, Iro system and hmu system, prophage genes, metabolism (sugar metabolism and D-serine catabolism), K1 capsule biosynthesis, and invasins such as CNF1 was affected, suggesting their role in bacteremia. The characterization of these genomic islands should reveal mechanisms of E. coli K1 pathogenicity that could be of value as therapeutic targets.